Determination of Gel Products in Alkali-Activated Fly Ash-Based Composites Incorporating Inorganic Calcium Additives - Haoyu Wang; Xianhui Zhao; Ting Wang; Lei Su; Boyu Zhou; Yonghui Lin (Advances in Materials Science and Engineering)
The introduction of soluble calcium additives contributes to forming calcium-containing geopolymer (N,C)-A-S-H and/or calcium (alumino)silicate hydration C-(A)-S-H in alkali-activated fly ash-based composites (AAFCs). However, the quantitative determination of the final gel product has yet been unclear due to the different chemical components, which influences the prediction of mechanical strength and microstructure. This study aims to propose a method to clarify the gel products in AAFCs by the critical elemental compositions in gel products. Furthermore, the AAFCs were prepared (by casting method) using soda residue (SR) as the calcium additive, fly ash as the aluminosilicate precursor, and sodium silicate solution as the alkaline activator. The compressive strengths of the AAFCs with different SR contents were recorded. The microstructures and gel products of AAFCs were detected through scanning electron microscope (SEM), energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD), and 29Si nuclear magnetic resonance spectrometer (29Si NMR). Finally, the proposed determination method was verified with the experimental results. The new proposed quantitative method refers to a limit value of 2Ca/Al = 1.00 about the critical chemical elements in gel products, which helps to determine the calcium-containing geopolymer (N,C)-A-S-H or/and calcium (alumino)silicate hydration C-(A)-S-H in stable AAFCs. Results show that the gel products are determined as single (N,C)-A-S-H gels when 2Ca/Al is lower than 1.00; meanwhile, (N,C)-A-S-H and C-(A)-S-H gels coexist when 2Ca/Al is higher than 1.00 by the above proposed quantitative determination method. Furthermore, it works that the industrial solid waste SRs regarded as calcium additive are applied in the AAFCs to verify the gel products by 2Ca/Al = 1.00 as the limit value. The results provide the theoretical and experimental basis for the performance prediction and microstructural determination.